2015
DOI: 10.4049/jimmunol.1500153
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Dysbiosis Due to Helicobacter Drives an Increase in Marginal Zone B Cells in the Absence of IL-10 Signaling in Macrophages

Abstract: It is clear that IL-10 plays an essential role in maintaining homeostasis in the gut in response to the microbiome. However, it is unknown whether IL-10 also facilitates immune homeostasis at distal sites. To address this question, we asked whether splenic immune populations were altered in IL-10-deficient (Il10−/−) mice in which differences in animal husbandry history were associated with susceptibility to spontaneous enterocolitis that is microbiome-dependent. The susceptible mice exhibited a significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 71 publications
(104 reference statements)
2
21
0
Order By: Relevance
“…For this reason, we cohoused both the control and Mpo −/− mice with mice from the Dittel colony prior to EAE induction to equilibrate their microbiomes. In support of this EAE induction protocol is our studies in Il10 −/− mice where we found that their T-independent immune responses were altered in a microbiome-dependent manner due to a significant increase in marginal zone B cells (Ray et al 2015). We also found that Il10 −/− mice from our colony harbored a different microbiome as compared to similar mice purchased directly from The Jackson Laboratory (Jax) and upon cohousing with mice from the Dittel colony their microbiomes shifted to that of the home colony (Ray et al 2015).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…For this reason, we cohoused both the control and Mpo −/− mice with mice from the Dittel colony prior to EAE induction to equilibrate their microbiomes. In support of this EAE induction protocol is our studies in Il10 −/− mice where we found that their T-independent immune responses were altered in a microbiome-dependent manner due to a significant increase in marginal zone B cells (Ray et al 2015). We also found that Il10 −/− mice from our colony harbored a different microbiome as compared to similar mice purchased directly from The Jackson Laboratory (Jax) and upon cohousing with mice from the Dittel colony their microbiomes shifted to that of the home colony (Ray et al 2015).…”
Section: Discussionmentioning
confidence: 69%
“…In support of this EAE induction protocol is our studies in Il10 −/− mice where we found that their T-independent immune responses were altered in a microbiome-dependent manner due to a significant increase in marginal zone B cells (Ray et al 2015). We also found that Il10 −/− mice from our colony harbored a different microbiome as compared to similar mice purchased directly from The Jackson Laboratory (Jax) and upon cohousing with mice from the Dittel colony their microbiomes shifted to that of the home colony (Ray et al 2015). From these data and other studies in the literature demonstrating that immunodeficiencies can alter the penetrance of disease in a putatively microbiome-dependent manner (Ray et al 2015, Ray & Dittel 2015), it is probable that since MPO is required for controlling certain bacterial and fungal infections, its absence could lead to a change in the composition of the microbiota altering EAE severity (Aratani et al 2000).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Exogenous bacteria can also trigger the development of immunogenic responses under certain conditions. For instance, the introduction of Helicobacter hepaticus in the presence of genetically-deficient interleukin-10 signalling systems led to an increase in pro-inflammatory marginal zone B cells (in the category of white blood cells, expressing antibodies) of the spleen [112]. The microbiome also controls the development of appropriate immunosuppression in response to dietary antigens through the production of immunosuppressive regulatory T-cells [113].…”
Section: Bacteria–brain Signallingmentioning
confidence: 99%
“…Thus, without the anti-inflammatory actions of IL-10, an unregulated Th1-mediated immune response against selected enteric bacteria ensues and precipitates colitis characterized histologically by epithelial hyperplasia, mucosal and submucosal inflammation, and ulcerative lesions in the cecal-colonic junction (26,(34)(35)(36)(37)(38). EHS infection exacerbates the onset of disease in IL-10 Ϫ/Ϫ mice and thus is a frequently used model to study pathogen-induced IBD and colon cancer.…”
Section: Discussionmentioning
confidence: 99%